A Mixed Methods Investigation of Posttraumatic Growth in Young Adults Following Parental Divorce. (April 2018) - Milam, Sarah R. B.; Schmidt, Christa K.
The present study used a mixed methods design to examine factors contributing to posttraumatic growth (PTG) in 232 young adults who experienced parental divorce. Participants completed an online survey including measures of social support, religious coping, posttraumatic stress, and posttraumatic growth. Participants also responded to five open-ended questions related to their parents' divorce. Multiple regression analysis demonstrated that perceived social support, intrinsic religiousness, and positive and negative religious coping contributed statistically significant variance to PTG. Qualitative data revealed themes of both pain and positive growth following parental divorce. Implications to assist children in the promotion of positive growth after parental divorce are discussed.